Spatially explicit models of seed availability improve predictions of conifer regeneration following the 2018 Carr Fire in northern California - Wright, Micah; van Mantgem, Phillip; Buffington, Kevin; Thorne, Karen; Engber, Eamon; Smith, Sean (Frontiers in Ecology and Evolution, 2023)
Article pending final approval and publication.